"Your Kung Fu is very good, Master Fiore!" Asian and European fight books in comparison - Wetzler Sixt (Bern Open Publishing, 2016)
The phenomenon of the fight book is not restricted to the European tradition. Similar artefacts, usually combining text and image to describe the techniques of close quarter combat with and without weapons, exist also in various Asian cultures, in China, Japan, Korea, and India. In the article, the question shall be raised in how far and to which end fight books of different cultures can be taken into one perspective, and be compared. To do so, similarities and dissimilarities between European and early Chinese fight books will be pointed out, and preliminary areas for comparison will be introduced. The aim of the article is to raise awareness for the topic, and to lay the ground for further discussion between specialists on the respective European and Chinese fields.